Purification and Characterization of a Novel Bacteriocin Produced by Enterococcus faecalis Strain RJ-11 - Yamamoto, Yukio (American Society for Microbiology, 2003)
Lactic acid bacteria exhibiting activity against the gram-positive bacterium Bacillus subtilis were isolated from rice bran. One of the isolates, identified as Enterococcus faecalis RJ-11, exhibited a wide spectrum of growth inhibition with various gram-positive bacteria. A bacteriocin purified from culture fluid, designated enterocin RJ-11, was heat stable and was not sensitive to acid and alkaline conditions, but it was sensitive to several proteolytic enzymes. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis analysis revealed that enterocin RJ-11 had a molecular weight of 5,000 in its monomeric form. The amino acid sequence determined for purified enterocin RJ-11 exhibited high levels of similarity to the sequences of enterocins produced by Enterococcus faecium.